Recent Advances on Polymeric Beads or Hydrogels as Embolization Agents for Improved Transcatheter Arterial Chemoembolization (TACE) - Chen, Yun-Ping; Zhang, Jiang-Ling; Zou, Yanhong; Wu, Yun-Long (Frontiers in Chemistry, 2019)
Transcatheter arterial chemoembolization (TACE), aiming to block the hepatic artery for inhibiting tumor blood supply, became a popular therapy for hepatocellular carcinoma (HCC) patients. Traditional TACE formulation of anticancer drug emulsion in ethiodized oil (i.e., Lipiodol®) and gelatin sponge (i.e., Gelfoam®) had drawbacks on patient tolerance and resulted in undesired systemic toxicity, which were both significantly improved by polymeric beads, microparticles, or hydrogels by taking advantage of the elegant design of biocompatible or biodegradable polymers, especially amphiphilic polymers or polymers with both hydrophilic and hydrophobic chains, which could self-assemble into proposed microspheres or hydrogels. In this review, we aimed to summarize recent advances on polymeric embolization beads or hydrogels as TACE agents, with emphasis on their material basis of polymer architectures, which are important but have not yet been comprehensively summarized.